2019
DOI: 10.1039/c9tc03778k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis of inorganic halide perovskites: evolution of phase-purity, morphology, and photoluminescence

Abstract: Solvent-free mechanochemical synthesis of phase-pure inorganic halide perovskites is investigated in depth revealing several beneficial and detrimental effects of ball-milling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 37 publications
4
66
0
Order By: Relevance
“…The resulting powder particles are in the size range of micrometers ( Fig. S7(d) in the ESM), which is expected and consistent with literature reports [38,39]. In its own turn, the nano-sized perovskite NPs can be prepared in the presence of h-PMMA as shown in Fig.…”
Section: Formation and Phase Conversion Of The Nanoparticlessupporting
confidence: 89%
“…The resulting powder particles are in the size range of micrometers ( Fig. S7(d) in the ESM), which is expected and consistent with literature reports [38,39]. In its own turn, the nano-sized perovskite NPs can be prepared in the presence of h-PMMA as shown in Fig.…”
Section: Formation and Phase Conversion Of The Nanoparticlessupporting
confidence: 89%
“…It was shown that Cs and MA‐containing lead halides as well as various mixed cation and anion compositions can be relatively easily prepared in a matter of minutes by manual grinding or milling the mixtures of corresponding binary halides . Since no solvent is used, the procedure is often claimed to be ‘solvent free’ . However, in most cases the raw materials, AX (A‐MA, Cs) and PbX 2 , are used for the synthesis ‘as received’, without any preliminary purification, and since both methylammonium and cesium halides are hygroscopic compounds, the starting mixture AX+PbX 2 may contain some unknown amount of water even if weighing and subsequent grinding or milling are carried out in the dry atmosphere.…”
Section: Results Of 15 Min Mechanochemical Activation Of Stoichiometrmentioning
confidence: 99%
“…If synthesis is done under ambient atmosphere, then water impact may be even stronger. This may, at least partially, explain the huge scatter, from about 5 min to several hours, in the reported mechanochemical reaction times necessary for obtaining single‐phase APbX 3 perovskite halides . Moreover, the mechanism of the mechanochemical formation of APbX 3 halides still has not received adequate attention, although this is obviously the key to optimization of the synthesis procedure in order to produce high‐quality single‐phase perovskite halides within the shortest possible time.…”
Section: Results Of 15 Min Mechanochemical Activation Of Stoichiometrmentioning
confidence: 99%
“…This is in agreement with previous reports. [21,30] When increasing amounts of SnBr 2 are added as replacement of PbBr 2 , we do not observe significant changes in the diffraction pattern, except a gradual shift toward higher angles (see Figure S1a for a better visualization, Supporting Information). This is ascribed to a shrinkage of the unit cell which is expected as Sn 2+ has a lower ionic radius than Pb 2+ .…”
mentioning
confidence: 83%